2018
DOI: 10.1371/journal.pone.0204400
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mRNA expression changes associated with field exposure to DDTs in chickens from KwaZulu-Natal, South Africa

Abstract: The objective of this study was to identify potential mRNA expression changes in chicken livers associated with environmental exposure to dichloro-diphenyl-trichloroethane (DDT) and its metabolites (DDTs). In particular, we focused on genes relating to the immune system and metabolism. We analyzed liver samples from free-ranging chickens in KwaZulu-Natal, South Africa, for contamination by DDTs. This area predominantly uses DDT in its malaria control program, and homes are sprayed annually with the pesticide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 66 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…A similar effect was repored previously 48 , when mLTC1 treatment with p,p′DDT lead to reduction of progesterone production. However, in that case there was no change in testosterone secretion and authors suggested that this may be due to up-regulation of CYP17 gene as reported earlier 49 . The reason for the no change in testosterone may be due to the cell model that we used.…”
Section: Discussionsupporting
confidence: 46%
“…A similar effect was repored previously 48 , when mLTC1 treatment with p,p′DDT lead to reduction of progesterone production. However, in that case there was no change in testosterone secretion and authors suggested that this may be due to up-regulation of CYP17 gene as reported earlier 49 . The reason for the no change in testosterone may be due to the cell model that we used.…”
Section: Discussionsupporting
confidence: 46%
“…For instance, residues of DDT, dichlorodiphenyl dichloroethane (DDD) and dichlorodiphenyl dichloroethylene (DDE) (DDT"s breakdown products) were found in water, sediment, vegetables and tissue samples collected from domestic chickens, wild birds and fish in the Limpopo Province of South Africa (18)(19)(20). Other parts of South Africa also reported high concentrations of DDT in birds (21)(22)(23), bird eggs (23)(24)(25), and fish (26,27).…”
Section: Current Use Of Ddt: Indoor Residual Spraying (Irs)mentioning
confidence: 99%
“…The contamination of terrestrial species by DDTs living in Phongolo region, our study area, has also been reported. High levels of DDT (36−14,398 n g/g ww) were detected in the livers of free ranging chickens [10] and in chicken eggs (5,200–48,000 n g / g ww DDTs) [9]. High concentrations of DDT in rat liver samples were also recorded in Ethiopia, where a similar study was conducted [11] in regions where DDT was being used for IRS for malaria vector control (Table 1).…”
mentioning
confidence: 99%